Analisis Kompetensi Guru dalam Mempersiapkan Media Pembelajaran Berbasis Teknologi Informasi Era Revolusi Industri 4.0 - Rahim, Fanny Rahmatina; Suherman, Dea Stevani; Murtiani, Murtiani (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Indonesia faces the biggest challenge in education. Various problems have arisen including teachers not yet utilizing technology optimally in learning. Teachers in schools still maintain conventional learning. Actions to motivate teachers are needed so that integrated learning of information technology can be implemented well. This is in accordance with the demands of the industrial revolution 4.0 in the learning process where teachers and students together make innovations including the use of information technology-based learning media. To find out how deep the teacher's understanding of the preparation of information technology-based learning media in the revolution era 4.0, analysis in the form of quantitative data presented descriptively is needed.